2022
DOI: 10.1007/s10113-021-01867-y
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence linking financial assistance for drought-affected agriculture and resilience in tropical Asia? A systematic review

Abstract: Agriculture is sensitive to drought and associated social, environmental and economic impacts. Finance-based interventions aim to support farmers affected by drought; however, the extent to which such tools encourage resilience to this natural hazard is unclear. This paper systematically reviews evidence on links between financial interventions to mitigate drought-related impacts and adaptation towards longer-term resilience. We focus on tropical Asia where agriculture contributes significantly to national eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 68 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Another explanation is that many financial services do not consider the seasonal investment and revenue opportunities of farmers or the sources of risk they confront, so farmers may not be entitled for or concerned in adopting the financial products, and they may not be beneficial even if they execute. Designing financial products around farmers’ particular financial requirements during any stress period can have potential impacts at micro as well as macro scales on improving food security for the poor communities of worldwide ( Goodwin et al, 2022 ).…”
Section: Future Directions Suggestions and Challenges In Action Agendamentioning
confidence: 99%
“…Another explanation is that many financial services do not consider the seasonal investment and revenue opportunities of farmers or the sources of risk they confront, so farmers may not be entitled for or concerned in adopting the financial products, and they may not be beneficial even if they execute. Designing financial products around farmers’ particular financial requirements during any stress period can have potential impacts at micro as well as macro scales on improving food security for the poor communities of worldwide ( Goodwin et al, 2022 ).…”
Section: Future Directions Suggestions and Challenges In Action Agendamentioning
confidence: 99%
“…In a review of governmental financial assistance in Tropical Asian countries, Goodwin et al. (2022) found that even when institutional schemes are available, high levels of social vulnerability prevent many potential beneficiaries from accessing them, therefore leaving vulnerable communities/sectors (e.g., farmers) with little to no options to cope with drought impacts. The impacts of droughts, however, are not only exacerbated or ameliorated by social, economic, or institutional factors that influence societal susceptibilities and the ability of communities economic sectors and systems to cope and adapt, but are also directly linked to physical and biological factors determining the susceptibility of ecosystems and the services they provide (Figure 1, panel a).…”
Section: A Novel Systemic Frameworkmentioning
confidence: 99%
“…For example, the 2018 drought event that led to widespread water shortages and almost to "Day Zero" in Cape Town has shown that human actions exacerbated the drought hazard (here: streamflow, reservoir and groundwater storage) through overconsumption, but also that socio-economic disparities influenced access to information as well as the choices households had to prepare for and cope with the drought (Savelli et al, 2021(Savelli et al, , 2023Ziervogel, 2019). In a review of governmental financial assistance in Tropical Asian countries, Goodwin et al (2022) found that even when institutional schemes are available, high levels of social vulnerability prevent many potential beneficiaries from accessing them, therefore leaving vulnerable communities/sectors (e.g., farmers) with little to no options to cope with drought impacts. The impacts of droughts, however, are not only exacerbated or ameliorated by social, economic, or institutional factors that influence societal susceptibilities and the ability of communities economic sectors and systems to cope and adapt, but are also directly linked to physical and biological factors determining the susceptibility of ecosystems and the services they provide (Figure 1, panel a).…”
Section: A Novel Systemic Frameworkmentioning
confidence: 99%
“…Agriculture is the source of life for a country and the economic lifeline of a country or region (Goodwin et al, 2022). With the vigorous development of modern economy, the influence of agriculture is also increasing day by day.…”
Section: Introductionmentioning
confidence: 99%